2010
DOI: 10.1152/ajpheart.01022.2009
|View full text |Cite
|
Sign up to set email alerts
|

Tissue oxygenation after exchange transfusion with ultrahigh-molecular-weight tense- and relaxed-state polymerized bovine hemoglobins

Abstract: Hemoglobin (Hb)-based O(2) carriers (HBOCs) constitute a class of therapeutic agents designed to correct the O(2) deficit under conditions of anemia and traumatic blood loss. The O(2) transport capacity of ultrahigh-molecular-weight bovine Hb polymers (PolybHb), polymerized in the tense (T) state and relaxed (R) state, were investigated in the hamster chamber window model using microvascular measurements to determine O(2) delivery during extreme anemia. The anemic state was induced by hemodilution with a plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…This pattern is consistent with PolybHb (the P 50 is 41 mm Hg for 50:1 T-state PolybHb and 0.66 mm Hg for 40:1 R-state PolybHb). 21,22 Both PolyhHbs show no cooperativity. Polymerization of hHb freezes the structure of hHb in a well-defined quaternary state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern is consistent with PolybHb (the P 50 is 41 mm Hg for 50:1 T-state PolybHb and 0.66 mm Hg for 40:1 R-state PolybHb). 21,22 Both PolyhHbs show no cooperativity. Polymerization of hHb freezes the structure of hHb in a well-defined quaternary state.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] PolyhHb synthesis T-state PolyhHb was synthesized as previously described in the literature. 9,[21][22][23] hHb was diluted with 20 mM phosphate buffer (PB; pH 8.0) to yield 1.5 L of 0.3 mM hHb that was stored in a 2 L glass bottle submerged in an ice bath. The contents of the glass bottle were then subjected to vacuum for 1 min, followed by argon purging for 1 min.…”
Section: Hb Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The arteriole diameter, average blood velocity and discharge hct ( H D ) for these simulations were taken from experimental data reported in reference [39] and personal communications from Dr. Cabrales (Bioengineering Department) at the University of California, San Diego (UCSD): the H D was set to 11% to mimic animal studies conducted using 50:1 L-PolyHb and 40:1 H-PolyHb solutions, while the H D was set to 18% to mimic animal studies conducted using 20:1 and 30:1 L- and H-PolyHb solutions. The radius of the RBC-rich region ( r 1 ) changes proportionally with the H D [58, 59], and the r 1 value used in this work was extrapolated from values of r 1 measured at hct s of 20%, 30% and 40% that were obtained from the literature [59].…”
Section: Mass Balance On O2/no With Hb Encapsulated Within Rbcs and Hmentioning
confidence: 99%
“…In the physiological range of observed blood vessel wall shear stresses ranging from 6–25 dyne/cm 2 , the rate of release of NO was found to be linearly dependent on the shear stress acting on the blood vessel wall [34, 35]. To further emphasize the importance of shear stress-induced NO production, Cabrales et al reported that transfusion of high viscosity >500 kDa fraction of ultrahigh molecular weight (MW) glutaraldehyde polymerized bHb (PolyHb) solutions synthesized by our group [36, 37] elicited little to no vasoconstriction in a hamster top-load model [38] and in an exchange transfusion model [39], while the commercial low MW polymerized HBOC Oxyglobin ® (average MW ~ 200 kDa) elicited severe hypertension [40], although these various PolyHbs possessed NO dioxygenation rate constants that were similar to that of cell-free Hb. Compared to Oxyglobin ® (1.8 cP at a total Hb concentration of 13 g/dL) [39], the viscosities of PolyHbs synthesized by our group are much higher than that of Oxyglobin ® (3.6 – 14 cP at a total Hb concentration of 10 g/dL).…”
Section: Introductionmentioning
confidence: 99%